Effects of Shift Work on Cognitive and Motor Performance in Nurses: A Systematic Review and Meta‐Analysis. - Ulupınar, Fadime; Ulupınar, Süleyman (Worldviews on Evidence-Based Nursing (John Wiley & Sons, Inc.), 2025)
Background: Shift work—especially during night hours—adversely affects nurses' cognitive and motor performance, potentially compromising patient safety. Variations in shift duration and rotation patterns contribute to these effects. Implementing evidence‐based strategies such as optimized scheduling, structured rest breaks, and supportive work environments may mitigate performance declines. These findings highlight the importance of organizational policies aimed at protecting both healthcare workers and patient outcomes. Methods: A comprehensive search across PubMed, Cochrane Library, and Web of Science identified 22 studies with 224 comparison data points for inclusion. Study quality was assessed using the ROBINS‐I tool across seven bias domains. Analyses were performed using Python, applying random‐effects models to account for heterogeneity (Cochran's Q, I2), with Egger's test used for publication bias assessment. Results: Day shifts led to a small performance decline (Hedges' g = 0.238, 95% CI [0.155, 0.321]), while night shifts caused a more substantial decline (Hedges' g = 0.386, 95% CI: 0.320 to 0.451). Motor performance across all shift types showed a moderate effect size (Hedges' g = 0.326, 95% CI [0.210, 0.442]). Comparing day shifts to nonstandard shifts, a small effect size (Hedges' g = 0.220, 95% CI [0.171, 0.269]) highlighted reduced performance under irregular shift conditions. High heterogeneity in night shifts (I2 = 86.8%) suggested variability in study designs and methodologies. Linking Evidence to Action: Shift work, particularly night shifts, negatively impacts cognitive and motor performance, posing risks to clinical safety. The variability in shift durations (6–17 h) and different shift rotation strategies contributed to heterogeneity. Targeted interventions, including optimized scheduling, adequate rest breaks, and supportive workplace practices, are needed to mitigate negative effects. This meta‐analysis provides evidence‐based insights into the detrimental effects of shift work on nurses' performance, supporting the development of policies and strategies to promote safer clinical environments and enhance healthcare quality. Trial Registration: PROSPERO